Relevant characteristics in the business behavior. Application in the curricular transformation in an Ecuadorian university - Carvajal Pérez, Luis Alfredo; Quinde Sari, Freddy Richard; Agudelo Casanova, Haiber Gustavo (SATHIRI, 2023)
In Ecuador, as well as in the world, it is evident that most companies were created by entrepreneurs’ ideas. The problem is the gap that exists between students who want to undertake and those who evidence the creation of a company during their career. The objective of this study is to validate the most relevant entrepreneurial behaviours of the State Polytechnic University of Carchi (UPEC) students, which contributes to modify the curriculum. Students measure 50 assertions with Likert scale which expose behaviours related to 10 business behaviours, allowing an Exploratory Factor Analysis (EFA) to explain the needs raised by McClelland in four latent variables such as: determined, effective, systematic, and safe. This statistical exercise fulfills the assumption of multivariate normality using the Mardia test and the Kayser Meyer Olkin (KMO) test, whose threshold must be greater than the value of Maximum Likelihood Extraction and Promax Rotation methods. Confirmatory Factor Analysis (CFA) was applied and the psychometric assumptions were validated: FC, AVE and VD. The results show how in Ecuador, some curriculum variables can be intervened, to make the students with entrepreneurial ideas become entrepreneurs. These students are systematic because they plan projects with pertinent information and execute the roadmap. They are effective, so they strive to deliver as planned. They are confident, since they confident in succeeding, and do excellent work to achieve inclusive solutions.
Keywords: Entrepreneurial behaviors; business thinking; exploratory factor analysis; confirmatory factor analysis; measurement model